The Use of HelloTalk for Seventh Graders' Vocabulary Mastery at SMPN 1 Prambon - Firosa Faizati; Iin baroroh Ma'arif; Ulfa Wulan Agustina; Luluk Choirun Nisak Nur (MASALIQ, 2026)
Vocabulary mastery is fundamental to English language learning because it supports effective communication across listening, speaking, reading, and writing; however, many junior high school students experience difficulties acquiring vocabulary because of limited exposure to authentic language use and the continued predominance of conventional instructional practices. This study aimed to examine the effect of the HelloTalk application on students’ vocabulary mastery and explore students’ and their teacher’s perceptions of its implementation in English language learning. A mixed-methods approach with a convergent parallel design was employed, involving 32 seventh-grade students and one English teacher at SMPN 1 Prambon. Quantitative data were collected through vocabulary pretests and posttests and analysed using descriptive and inferential statistics, whereas qualitative data were obtained through questionnaires, interviews, and classroom observations and analysed through data reduction, data display, conclusion drawing, and verification. The findings showed that the students’ mean vocabulary score increased from 78.8 on the pretest to 92.3 on the posttest, demonstrating improved vocabulary mastery following the implementation of HelloTalk. The qualitative findings further revealed positive perceptions among the students and teacher, particularly regarding the application’s interactive features, ease of use, opportunities for authentic communication, and contribution to students’ motivation and confidence in learning English. The study concludes that HelloTalk can serve as an effective mobile-assisted language learning application for enhancing vocabulary mastery and facilitating more interactive, authentic, and learner-centred English instruction. These findings contribute empirical evidence regarding the pedagogical value of mobile-assisted language learning and provide practical implications for English teachers seeking to integrate communication-based digital applications into vocabulary instruction.